Sistem bantu keputusan untuk Sekolah Menengah Islam Hidayah - Tarmidi, Mohammad Zakri (2008)
The process to evaluate student performance is very important to help the school administration to improve student achievement. Decision Support System for Hidayah Islamic Secondary School is the system that will be use to make decision for student selection for leadership, sahsiah and co-curriculum based on student performance based on academic, sahsiah and co-curriculum aspect. These three aspects has become foundation for this school education. This system has been developed to help the school administration such as Headmaster, Assistant Headmaster and School Committee. With this system, it will help the parent, student, and teacher to insert data and reviewing the data in such manner. The information processing can be faster and it also reduces the processing cost using weighted linear programming with academic, sahsiah and co-curriculum as a component. With this system, it helps school administration to make a decision about student performance faster and cheaper.